2023
DOI: 10.1039/d3cp03587e
|View full text |Cite
|
Sign up to set email alerts
|

Bulk nanostructure of a deep eutectic solvent with an amphiphilic hydrogen bond donor

Lucas N. Wong,
Silvia. Imberti,
Gregory G. Warr
et al.

Abstract: Neutron diffraction with empirical potential structure refinement shows that the deep eutectic solvent 1 : 4 choline chloride : butyric acid is an amphiphilically nanostructured liquid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 79 publications
(159 reference statements)
0
2
0
Order By: Relevance
“…Of these g ij ( r )­s, the highest coordination number is between the Ch + nitrogen and water oxygen, revealing that water tends to hydrate the Ch + charge center. The strong interaction between water and Ch + is also observed in aqueous mixtures of cholinium-deep eutectic solvents. …”
Section: Resultsmentioning
confidence: 96%
“…Of these g ij ( r )­s, the highest coordination number is between the Ch + nitrogen and water oxygen, revealing that water tends to hydrate the Ch + charge center. The strong interaction between water and Ch + is also observed in aqueous mixtures of cholinium-deep eutectic solvents. …”
Section: Resultsmentioning
confidence: 96%
“…36 McDonald et al have shown small-angle nanostructure in binary DES engineered to contain long alkyl subunits, 37 which has recently also been shown for choline chloride : butyric acid DES. 38 However, the question of nanostructure in archetypal, non-amphiphilic DES such as ChCl-urea, remains open and debated, and the same is true for ternary DES; 39 this issue is therefore important to resolve considering the popularity of these systems. Since ChCl-urea is the most widely used DES in studies of amphiphile self-assembly, we have chosen this system as a model starting point towards myriad future studies, expanding on the possibilities of solute organisation in such solvents.…”
Section: Introductionmentioning
confidence: 99%